Potensi Antilmintik Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi) Secara In Vivo Terhadap Cacing Intestinum Ayam Kampung (Gallus domesticus) - Moenek, Devi Y.J.A.; Toelle, Novianti N.; Oematan, Aven B. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
Native chicken has a very big role in people's lives because it can be used as a source of meat and eggs to the nutritional needs of the community, especially animal protein, as well as additional income. However, Native chickens also have the disadvantage of being easily infected with parasites in their environment. The parasites that often infect chickens are nematodes and cestodes. One alternative treatment for helminthiasis that does not produce chemical residues is to use the Belimbing wuluh plant (Averrhoa bilimbi). The part of the starfruit plant that has benefits as an anti-parasitic is the leaves. Belimbing wuluh leaves contain flavonoid, tannins, and saponins compounds that function as antiparasitic. This study aims to determine the potential of starfruit leaf extract (Averrhoa bilimbi) as an anthelmintic against intestinal worms in native chickens (Gallus domesticus) administered in vivo. The research method used is experimental with the experimental design used is Completely Randomized Design (CRD) with 3 treatments and 5 replications. The concentration of starfruit leaf extract were 25%, 30%, and 35%. The technique of collecting data was by observation (direct observation) by observing the presence of worms in the intestines of native chickens after giving Belimbing wuluh leaves extract (Averrhoa bilimbi). The data from this research are presented in the form of images, all data are then analyzed descriptively. The results of the laboratory examination showed 15 samples of chicken intestine that were tested positive for worms. This indicates that the leaf extract of belimbing wuluh with concentrations of 25%, 30%, and 35% given pharmacokinetically to native chickens was not able to control Ascaridia galli and Raillietina sp.